Characteristics Of Decisional Participation By Nurses - Alutto, Joseph A.; Vredenburgh, Donald J. (Academy of Management Journal, 1977)
The article discusses a 1977 study on the decision-making involvement of nurses in the health care industry. The conceptualization of decisional participation was done by means of a construct contrasting current and preferred patterns of participation in a specific nursing role decisions. The study indicates that individuals desiring more decision-making involvement experienced higher job tension and higher career dissatisfaction. An alternate study found that decision deprivation may be attributed to lower levels of satisfaction with promotion, pay, work, and supervision.